2015
DOI: 10.1007/s10549-015-3355-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic associations of 25 hydroxy vitamin D in NCIC CTG MA.21, a phase III adjuvant randomized clinical trial of three chemotherapy regimens in high-risk breast cancer

Abstract: Low vitamin D levels have been associated with poor breast cancer outcomes in observational studies. We examined the association of vitamin D blood levels with relapse-free survival (RFS), breast cancer-specific survival (BCSS), and overall survival (OS) in the MA.21 randomized clinical trial. Fasting blood was collected pre-chemotherapy in 934/2104 (44.4 %) of subjects; 25 hydroxy vitamin D was measured (radioimmunoassay, Diasorin) in one batch. Vitamin D was assessed as a transformed continuous factor, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…The mechanistic evidence is in agreement with observational data supporting an adverse association between breast cancer recurrence and levels of serum 25-hydroxyvitamin D [25(OH)D], the precursor to calcitriol [43, 44]. In contrast, findings from observational studies contradict these results, as no associations between serum 25(OH)D levels and breast cancer outcomes have been observed in a secondary analysis of the WHEL data [38], or in adjuvant (MA.21 [40•], MA.14 [41]) or neo-adjuvant (I-SPY [39]) settings. Although the nesting of observational studies in randomized trials such as that in Clark et al [39], Lohmann et al [40•], and Pritchard et al [41] has its limitations, the RCTs provide greater standardization of tumor, treatment, and outcome characterizations than the non-therapeutic observational studies.…”
Section: Diet and Risk Of Breast Cancer Recurrencesupporting
confidence: 78%
See 2 more Smart Citations
“…The mechanistic evidence is in agreement with observational data supporting an adverse association between breast cancer recurrence and levels of serum 25-hydroxyvitamin D [25(OH)D], the precursor to calcitriol [43, 44]. In contrast, findings from observational studies contradict these results, as no associations between serum 25(OH)D levels and breast cancer outcomes have been observed in a secondary analysis of the WHEL data [38], or in adjuvant (MA.21 [40•], MA.14 [41]) or neo-adjuvant (I-SPY [39]) settings. Although the nesting of observational studies in randomized trials such as that in Clark et al [39], Lohmann et al [40•], and Pritchard et al [41] has its limitations, the RCTs provide greater standardization of tumor, treatment, and outcome characterizations than the non-therapeutic observational studies.…”
Section: Diet and Risk Of Breast Cancer Recurrencesupporting
confidence: 78%
“…Though evidence from in vitro, animal, and observational studies support the role of vitamin D in improving breast cancer outcomes, data from prospective [38] and observational studies nested randomized trials [39, 40•, 41] in women with breast cancer have not suggested prognostic associations [39, 40•, 41]. The physiological mechanism underpinning the inhibitory action of vitamin D on breast cancer centers on calcitriol, the hormonally active form of vitamin D. Calcitriol inhibits proliferation of human breast cancer cell lines and arrests tumor growth in xenograft models through several processes that ultimately suppress estrogen pathways in breast cancer cells (reviewed in Krishnan et al [42]).…”
Section: Diet and Risk Of Breast Cancer Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…Goodwin et al were the fi rst to report an association of Vitamin D blood levels with breast cancer outcomes (Goodwin et al 2009 ); there have been a number of subsequent studies examining serum 25(OH)D and breast cancer survival, with somewhat inconsistent results. Studies conducted outside of clinical trial settings have fairly consistently identifi ed signifi cant associations of low vitamin D with poor diseasefree or overall survival [reviewed in Rose et al ( 2013 )], while studies conducted in the setting of a clinical trial have failed to identify associations of vitamin D with outcomes (Lohmann et al 2014 ;Pritchard et al 2011 ). A recent systematic review concluded that circulating 25-OHD levels "may be associated with better prognosis in patients with breast cancer," but the included studies had mixed results (Toriola et al 2014 ).…”
Section: Blood Levels Of Vitamin Dmentioning
confidence: 99%
“…(BertoneJohnson et al, 2005;Abbas et al, 2008;Wang et al, 2013;Janowsky et al, 1999;Lyra et al, 2006;Hiatt et al, 1998;Gandini et al, 2011;Ordóñez-Mena et al, 2015;Yin et al, 2010). In addition, while 25(OH)D 3 deficiency was associated with poor outcome in observational studies (Goodwin et al, 2009), no prognostic association of 25 hydroxy vitamin D in a phase III adjuvant randomized clinical trial of chemotherapy regimens in high-risk breast cancer patients was observed (Lohmann et al, 2015). Hence, some controversies are still in place regarding the association between 25(OH)D 3 level and breast cancer risk and prognosis.…”
Section: Introductionmentioning
confidence: 99%